<=>\(1.x^2-1=3=>x^2=4=\left(+-2\right)^2=>x=+-2\)
Trả lời:
1, \(\left(x-1\right)\left(x+1\right)=3\)
\(\Leftrightarrow x^2-1=3\)
\(\Leftrightarrow x^2=4\)
\(\Leftrightarrow\orbr{\begin{cases}x=2\\x=-2\end{cases}}\)
Vậy S = { 2 ; - 2 }
2, \(\left(x-1\right)\left(x^2+x+1\right)-x\left(x-2\right)\left(x+2\right)=5\)
\(\Leftrightarrow x^3-1-x\left(x^2-4\right)=5\)
\(\Leftrightarrow x^3-1-x^3+4x=5\)
\(\Leftrightarrow4x-1=5\)
\(\Leftrightarrow4x=6\)
\(\Leftrightarrow x=\frac{3}{2}\)
Vậy \(S=\left\{\frac{3}{2}\right\}\)
3, 7x + 4 ( 5 - x ) = 3
<=> 7x + 20 - 4x = 3
<=> 3x + 20 = 3
<=> 3x = - 17
<=> x = - 17/3
Vậy S = { - 17/3 }
1. (x -1)(x + 1) = 3
=> x2 - 1= 3
=> x2 = 4
=> x 2 = 22
=> x = \(\pm2\)
2. (x - 1)(x2 + x + 1) - (x - 2)(x + 2)x = 5
<=> x3 - 1 - x3 + 4x = 5
<=> 4x = 6
<=> x = 1,5
3. 7x + 4(5 - x) = 3
<=> 7x + 20 - 4x = 3
<=> 3x = -17
<=> x = -17/3